2019
DOI: 10.1002/pbc.27977
|View full text |Cite
|
Sign up to set email alerts
|

Corticosteroid‐induced glaucoma in pediatric patients with hematological malignancies

Abstract: Background Corticosteroids, especially dexamethasone, play a critical role in chemotherapy for pediatric hematological malignancies. We previously observed that patients with complaints of headache or photophobia during corticosteroid administration had high intraocular pressure (IOP). Procedure We measured IOP during corticosteroid administration in 15 patients with acute leukemia or lymphoma undergoing treatment at our institution from January 2016 to December 2018. IOP was measured by an ophthalmologist wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 10 publications
3
23
0
1
Order By: Relevance
“…Since all children with ALL, regardless of their ALL phenotype, receive high‐dose dexamethasone therapy during the delayed intensification period, these findings raise grave concerns about the potential development of OHT. Our results are in line with previous reports indicating a higher prevalence of OHT in children treated with dexamethasone compared to prednisone 33 …”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Since all children with ALL, regardless of their ALL phenotype, receive high‐dose dexamethasone therapy during the delayed intensification period, these findings raise grave concerns about the potential development of OHT. Our results are in line with previous reports indicating a higher prevalence of OHT in children treated with dexamethasone compared to prednisone 33 …”
Section: Discussionsupporting
confidence: 93%
“…Our results are in line with previous reports indicating a higher prevalence of OHT in children treated with dexamethasone compared to prednisone. 33 Other factors that were associated with OHT in our cohort, in agreement with previous reports, were elevated BMI 36 and a family history of glaucoma. In addition, we report three novel findings associated with OHT in this setting.…”
Section: Risk Factors For Oht During Gc Therapy In Children With Allsupporting
confidence: 93%
See 2 more Smart Citations
“…Young age has been shown to be a considerable risk factor for ocular hypertension in children treated with topical steroid, and was also, in the present study, found to be a risk factor for systemic treatment since steroid responders were significantly younger than nonresponders. A similar observation was made by Sugiyama et al (2019) but not found by Hayasaka et al (2006).…”
Section: Discussionsupporting
confidence: 87%